2016
DOI: 10.1111/iju.13186
|View full text |Cite
|
Sign up to set email alerts
|

Providing prostate cancer survivorship care in Japan: Implications from the USA care model

Abstract: Despite an increasing number of prostate cancer survivors in Japan, the current delivery of prostate cancer survivorship care is insufficient and lacks a multidisciplinary approach. We carried out a study to characterize prostate cancer survivorship care in Japan, examine the Japanese workforce available to deliver survivorship care, introduce a conceptual framework for survivorship and identify opportunities to improve Japanese survivorship care. We systematically searched PubMed for prostate cancer survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…A recent review of several studies regarding prostate cancer survivorship found that prostate cancer survivors of different races might have different outcomes and needs concerning cancer control, expectations, general, urinary, bowel, and sexual QoL. 24 Because the overall satisfaction of patients in this study treated with PADT was superior to those treated with RP, it is possible that decreased physical and sexual functions were not important issues for the patients during the 1-year treatment period. The treatment decision, which patients made themselves, and the expectations of treatment may be more important for Japanese men treated for prostate cancer.…”
Section: Discussionmentioning
confidence: 82%
“…A recent review of several studies regarding prostate cancer survivorship found that prostate cancer survivors of different races might have different outcomes and needs concerning cancer control, expectations, general, urinary, bowel, and sexual QoL. 24 Because the overall satisfaction of patients in this study treated with PADT was superior to those treated with RP, it is possible that decreased physical and sexual functions were not important issues for the patients during the 1-year treatment period. The treatment decision, which patients made themselves, and the expectations of treatment may be more important for Japanese men treated for prostate cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Osawa et al . reported differences in the types of prostate cancer healthcare providers between Japan and the USA . There are huge costs required to educate and train physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Osawa et al reported differences in the types of prostate cancer healthcare providers between Japan and the USA. 40 There are huge costs required to educate and train physicians. Therefore, a supportive work environment for other cancer healthcare providers, such as certified nurse specialists, will be important to improve cancer healthcare.…”
Section: Subspecialties Of Japanese Urologistsmentioning
confidence: 99%